Behavior of Company Performance in Response to Dividend Policy: An Analysis of Textile Sector Listed in Pakistan Stock Exchange - Ahmad, Nisar; Ahmed, Ayesha (Archives of Business Research, 2021)
The current study explains the relationship of dividend payout policy on the business performance of companies that exist in textile of Pakistan. 100 companies are selected from textile sector. Relationship of dividend payout policy and business performance was controlled with four variables based on relevant theories. These variables include size of company, growth of company, leverage (debt to equity ratio) and corporate governance index. Panel data is collected from 2012-2017 (six years) and then analyzed with unit root, descriptive statistics, correlation analysis, OLS regression, Lagrange multiplier, Huasman test, Fixed effect and Random effect models. Following key findings for each research objective were obtained by applying the adopted research method on the data through the adopted method of analyses: The results of the study show that in textile companies, a negative relationship occurs between dividend payout policy and their profitability. Furthermore, size of the firm according to the pecking order theory and leverage as per the agency cost theory came out to have a significant controlling effect on this negative relationship.